Analysis of Asymmetry in the Price-Volume Relation: Evidence from the Pakistani Stock Market - Mubarik, Fauzia; Javid, Attiya Y. (Indian Journal of Finance, 2010)
Market participants keep a close eye on trading volume as it reflects the dynamic interplay between informed traders and uninformed traders who interact with each other and set market clearing prices. Volume represents the total number of shares traded for a given time period and measures the liquidity in a stock or index. The higher the volume, the narrower are the spreads, less slippage, and less volatility. Trading volume is viewed by traders as the critical piece of information that signals the price movements. Stock prices are usually influenced by positive trading volume through the available set of relevant information on the market. A revision in investors' expectations usually leads to an increase in trading volume, which eventually reflects the sum of investors' reaction to news. Trading volume either activates or deactivates the price movements.